A novel CaO–K2O–Na2O–P2O5 glass systems for radiation shielding applications. (November 2021) - Al-Harbi, Nuha; Sayyed, M.I.; Al-Hadeethi, Yas; Kumar, Ashok; Elsafi, M.; Mahmoud, K.A.; Khandaker, Mayeen Uddin; Bradley, D.A.
Abstract: A novel phosphate-based glass system was fabricated to be applied in some dental applications. The fabricated glass system consists of non-toxic CaO–K2 O–Na2 O– P2 O5 compounds and described by the chemical formula (40 + x) P2 O5 +20CaO+(30-x) Na2 O+10K2 O, where 0 = x ≤ 20 mol%. The absorption spectra of the fabricated glasses were recorded by the UV–Vis spectrophotometer in the wavelength range 200–1100 nm. The refractive index found to be decreased from 2.438 to 2.328, while the direct energy gap was enhanced from 3.626 to 3.880 eV with increasing the P2 O5 concentration. Moreover, the fabricated glass system's gamma-ray shielding capacity was examined using the Geant 4 simulation code, and compared with the NIST photon cross-section database (XCOM) in the energy region between 0.161 and 2.51 MeV. The highest linear attenuation coefficient (LAC) was obtained for glass samples with 40 mol% of P2 O5, varied between 0.326 and 0.091 cm −1 . In contrast, the lowest LAC was achieved for glass samples with 60 mol% of the P2 O5 compounds, decreased from 0.301 to 0.087 cm −1 when the gamma photon energy was raised from 0.161 to 2.51 MeV, respectively. Highlights: CaO–K2 O–Na2 O– P2 O5 glasses were fabricated. The absorption spectra were recorded by the UV–Vis between 200 and 1100 nm. The refractive index decreased from 2.438 to 2.328 with increasing P2 O5 content. The highest LAC was achieved for glass samples with 40 mol% of P2 O5 .